Electroencephalography Patterns of Subacute Sclerosing Panencephalitis - Ali, Saad (Cureus, 2021)
Introduction and background: This article explores the electroencephalography (EEG) pattern in patients of suspected subacute sclerosing panencephalitis (SSPE) visiting Lady Reading Hospital, Peshawar. Pakistan has a huge deficit of research culture, and limited studies are done on this topic. This study concluded that a typical pattern is the most common EEG pattern, although atypical and normal EEG patterns were also observed. It is worth inclusion into the existing literature and may be used for future literature review of similar studies done elsewhere in Pakistan to give a wider perspective comprised of a larger sample size - integrating all studies. Objective: To determine the frequency of different patterns of EEG (typical, atypical, and normal) in SSPE patients. Methodology: Seventy-seven patients of both male and female genders between ages one to 20 years, who were diagnosed with SSPE, were included in the study. Dyken’s criteria were used to diagnose the patients. A prior history of previous measles infection with signs and symptoms suggestive of SSPE and positive anti-measles IgG antibodies in the cerebrospinal fluid (CSF) was found in all the patients included in the study. Besides this, typical EEG patterns and raised CSF globulin levels were also used for confirmation of the diagnosis. All the patients fulfilling the above criteria and presenting to the neurology department of Lady Reading Hospital, Peshawar, from February 1, 2019, to November 30, 2019, were included in the study. All the patients underwent the EEG monitoring in the same EEG laboratory and were reported by the same consultant with careful exclusion of any artifacts during the study. Result: There were 59 (76.62%) males and 18 (23.37%) females. The mean age was 15 ± 8.6 years, and the mean duration of symptoms was 4.79 ± 1.68 months. EEG was normal in 14 (18.18%) patients, while 63 (81.81%) patients had an abnormal EEG pattern, with a majority of 53 (84.12%) patients showing periodic delta wave complexes. Only 10 (15.87%) patients showed atypical patterns. Conclusion: Almost all the patients of SSPE showed periodic high-amplitude delta waves complexes, which usually occurs in patients with a disease duration of more than four months. However, further studies with a large sample size are needed for the confirmation of this observation.